2021
DOI: 10.1038/s42003-021-01682-5
|View full text |Cite
|
Sign up to set email alerts
|

A human model of Batten disease shows role of CLN3 in phagocytosis at the photoreceptor–RPE interface

Abstract: Mutations in CLN3 lead to photoreceptor cell loss in CLN3 disease, a lysosomal storage disorder characterized by childhood-onset vision loss, neurological impairment, and premature death. However, how CLN3 mutations cause photoreceptor cell death is not known. Here, we show that CLN3 is required for phagocytosis of photoreceptor outer segment (POS) by retinal pigment epithelium (RPE) cells, a cellular process essential for photoreceptor survival. Specifically, a proportion of CLN3 in human, mouse, and iPSC-RPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 91 publications
(108 reference statements)
2
33
0
Order By: Relevance
“…Based on these findings, it might be reasonable to assume that the lysosome regulator PGRN is highly expressed in the RPE layer and may play a central role in the regulation of intercellular digestion of RPE. However, few studies have focused on the morphological and functional changes in RPE in CLN models [ 38 ]. Thus, future studies are needed to elucidate the exact functions of PGRN in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it might be reasonable to assume that the lysosome regulator PGRN is highly expressed in the RPE layer and may play a central role in the regulation of intercellular digestion of RPE. However, few studies have focused on the morphological and functional changes in RPE in CLN models [ 38 ]. Thus, future studies are needed to elucidate the exact functions of PGRN in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal ceroid lipofuscinoses (NCL), also referred to as Batten disease, are a collection of neurodegenerative lysosomal storage disorders characterized by an overaccumulation of lipofuscin, a fluorescent mixture of partially digested proteins and lipids, that progressively builds up with age in the lysosomes of various cell types, including neurons (Adler et al 2015 ; Tang et al 2021 ). Most neurodegenerative diseases tend to be present in adults and develop with advancing senility.…”
Section: Neurodegenerative Diseases: the Big Picturementioning
confidence: 99%
“…More recently, a study aimed to understand the role of CLN3 in retinal pigment epithelium (RPE) structure and function by generating iPSC-RPE cells from fibroblasts of CLN3 disease patients has implicated the contribution of the CLN3 gene in RPE dysfunction and photoreceptor outer segment (POS) phagocytosis in CLN3 disease [ 107 ]. The CLN3 iPSC-RPE cells showed an affected structure and function in a cell autonomous manner when compared to control; moreover, the RPE structure necessary for POS phagocytosis was also abnormal and decreased apical RPE microvilli density, and reduced POS binding was also observed which resulted in the lower uptake of POS by CLN3 iPSC-RPE cells.…”
Section: Ipsc-based Phenotypic Modeling For Drug Discovery In the Nclsmentioning
confidence: 99%
“…Consistent with the impaired lysosomal degradation of POS by RPE cells in CLN3 disease pathology [ 111 ], CLN3 in iPSC-RPE cells was colocalized with the lysosomal marker LAMP1. This study, therefore, suggested that RPE cells may be a crucial gene therapy target to combat the loss of vision phenotype in CLN3 disease [ 107 ].…”
Section: Ipsc-based Phenotypic Modeling For Drug Discovery In the Nclsmentioning
confidence: 99%